STUDENTS’ LEARNING STYLES IN LEARNING TRANSACTIONAL SPEAKING SKILLS - Nur, Nur Aliyah; Annisa Shofa Tsuraya,; Nurul Parah, (ETERNAL (English, Teaching, Learning, and Research Journal), 2022)
The diverse backgrounds of students in learning English lead to a great challenge to the teacher to accommodate different types of students’ learning styles. This research aims to identify the students’ learning styles in learning transactional speaking skills in the fourth semester students of English Education Department, UIN Alauddin Makassar. The method used in this research was the descriptive qualitative research method. The instrument used to gather the data were questionnaires and interview guidelines. The results showed that the students like to learn transactional speaking skills by watching videos or films, pictures or posters, talking to their friends, practicing their English outside, and making conversations with their friends. Besides, some students like studying alone, reading books in a foreign language, working problems set by the teacher, memorizing conversations or dialogue, and writing in a notebook. Based on the categorization of the learning styles as concrete, analytical, communicative, and authority-oriented learners, the researchers found that the dominant learning styles were concrete learners. Based on the findings, the researchers recommend that it is essential for the lecturers to implement learning and teaching methods that are appropriate to students’ learning styles when teaching transactional speaking skills in the classroom. In addition, the students are expected to be able to develop their transactional speaking skills by understanding their individual learning styles for better learning and teaching process.